Regulación fina de campo magnético por medio de resonancia magnética nuclear pulsada. - Cancino De Greiff, Héctor Fernando (Ingeniería, 1999)
This work is about the magnetic field control system modification that uses a Hall Probe as sensor element to convert it in a new discrete control system through using an NMR spectrometer. Considering that the gyromagnetic constant of resonance nucleus is unique for each chemical element, maintaining stable the excite frequency the obtained field should be supplied without any variation. Employing digital signal processing on detected signal, it is possible to obtain the required stability of the system, controlling the period of this signal and comparing it with a fixed measurement, we get a new control signal that permits the command of the plant. The feedback system presents an damped output to step excitation with reasonable peak that permits stabilization into an acceptable linear range.